2003
DOI: 10.1051/0004-6361:20030193
|View full text |Cite
|
Sign up to set email alerts
|

New light curve analysis and period changes of the overcontact binary XY Leonis

Abstract: Abstract. Light curves and photometric solutions of the contact binary XY Leo are presented. The UBVR light curves appear to be almost symmetric. The B and V light curves were analysed with the Wilson-Devinney code and the orbital parameters of the system were obtained and compared with those obtained in previous studies. All the times of minimum light were collected and combined with the new ones obtained in this study. The orbital period of the system oscillates with a period of 19.6 years and a semi-amplitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
25
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 26 publications
8
25
0
Order By: Relevance
“…Hence, a sinusoidal variation superimposed on an upward/downward parabola suggests mass transfer between the components of a binary system that has a third body orbiting it e.g. XY Leo (Yakut et al 2003), TY Boo (Yang et al 2007), V839 Oph (Akalin & Derman 1997), BB Peg (Kalomeni et al 2007). Usually, ephemeris of such a system is written as where the first two terms are linear, the third one is due to the period increase/decrease and the last term τ, is the light-time term, which was formalized by Irwin (1952) as…”
Section: New Ephemeris and Period Change Analysis Of Close Binariesmentioning
confidence: 99%
“…Hence, a sinusoidal variation superimposed on an upward/downward parabola suggests mass transfer between the components of a binary system that has a third body orbiting it e.g. XY Leo (Yakut et al 2003), TY Boo (Yang et al 2007), V839 Oph (Akalin & Derman 1997), BB Peg (Kalomeni et al 2007). Usually, ephemeris of such a system is written as where the first two terms are linear, the third one is due to the period increase/decrease and the last term τ, is the light-time term, which was formalized by Irwin (1952) as…”
Section: New Ephemeris and Period Change Analysis Of Close Binariesmentioning
confidence: 99%
“…Hilditch 1981; Kaluzny & Pojmanski 1983;Hrivnak 1985) attributed to the asymmetric distribution of cool spot regions on one or both components. The orbital period of the system changes with time, and O-C residuals, indicating the differences between the observed times of eclipses and the calculated ones using the light elements, were studied by Gehlich, Prolss & Wehmeyer (1972), Kaluzny & Pojmanski (1983), Hrivnak (1985), Pan & Cao (1998) and recently by Yakut et al (2003). In the latter paper it was shown that the orbital period of the system oscillates with a period of 19.6 years, with a semi-amplitude of 0.023 days.…”
Section: Xy Leomentioning
confidence: 99%
“…Also, Barden (1987) showed that a significant portion of the chromospheric emission observed by many investigators from XY Leo was, instead, associated with the components of the BY Dra binary, which together with XY Leo forms a quadruple system. Yakut et al (2003) analyzed the B and V light curves obtained during [2000][2001] with the 48 cm Cassegrain telescope at Ege University Observatory. They applied Wilson-Devinney code by assuming that there was a third light in the system.…”
Section: Xy Leomentioning
confidence: 99%
See 2 more Smart Citations